2017
DOI: 10.1016/j.trecan.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells, Cancer, and MUSASHI in Blood and Guts

Abstract: The mammalian MSI family of RNA binding proteins play important roles as oncoproteins in a wide array of tumors including leukemias, glioblastoma, and pancreatic, breast, lung, and colorectal cancers,. Interestingly, the mammalian Msi genes, Msi1 and Msi2 have been most thoroughly investigated in two highly proliferative tissues prone to oncogenic transformation: the hematopoietic lineage and the intestinal epithelium. Despite their vast phenotypic differences, Msi proteins appear to play an analogous role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 63 publications
2
61
0
Order By: Relevance
“…[15][16][17] As such, it mediates mRNA stability and translation of proteins involved in oncogenic pathways. [18][19][20] Overexpression and knockdown studies indicate that MSI2 is a promising therapeutic target for cancer. 3,13,16,21,22 Human MSI2 is a 328 amino acid protein that contains two RNA recognition motifs (RRMs) spanning G21-K111 (RRM1) and K110-P187 (RRM2).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] As such, it mediates mRNA stability and translation of proteins involved in oncogenic pathways. [18][19][20] Overexpression and knockdown studies indicate that MSI2 is a promising therapeutic target for cancer. 3,13,16,21,22 Human MSI2 is a 328 amino acid protein that contains two RNA recognition motifs (RRMs) spanning G21-K111 (RRM1) and K110-P187 (RRM2).…”
Section: Introductionmentioning
confidence: 99%
“…MSI2 is a master RNA‐binding protein and posttranscriptional regulator that primarily controls mRNA stability and translation (Kudinov et al, 2017). It maintains the undifferentiated state of stem cells and cancer cells, serves in tissue regeneration, and is controlled through Notch pathways of stem cells (Takahashi et al, 2013; Kharas and Lengner, 2017). Although MSI2 and its isoform MSI1 are more commonly found in neoplastic cells (Kudinov et al, 2017), MSI2 is expressed throughout the SCN, as shown in the current study, within neurons and GFAP‐positive astrocytes of SCN explant tissue before and after culture and in brain sections from perfused mice.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA altered by Msi2 KO, KD, and OE has been described in several tissues: skin (Bennett et al, 2016; Ma et al, 2017), intestinal epithelium (Wang et al, 2015), hematopoietic stem cells (Park et al, 2014; Rentas et al, 2016; Kharas and Lengner, 2017). As summarized in Table 3, these studies describe MSI2 effects on cell differentiation, migration, and cell‐cell interactions that may be relevant to any neurogenesis or circuit remodeling in the SCN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations